Enacting new freshwater geographies: Te Awaroa and the transformative imagination. (April 2014) - Salmond, Anne; Tadaki, Marc; Gregory, Tim; Tadaki, Marc; Fuller, Ian
Abstract Water is a central element of social and material life, and the institutions created around water embody societal values. While mainstream interpretations focus on the quantity and quality of water, we argue that a greater risk to the health of waterways is the philosophical disconnection between people and water, expressed through institutions and technologies of alienation. A structural response based on cultural transformation is needed, cultivating diverse institutions of care that enable communities to reconnect with their waterways based on more‐than‐economic relations. Te Awaroa seeks to transform long‐term relationships between people and water to ensure that waterways and their communities alike are in a state of ora (health, well‐being and prosperity).